Cost-effectiveness of open versus laparoscopic pancreaticoduodenectomy: a retrospective Markov model analysis from China - Zhu, Yan; Liu, Qi; Cheng, Hua; Shen, Xiaoding; Wang, Ziyao; Liang, Danmei; Ke, Nengwen; Zhang, Xiaoxia (Frontiers in Oncology, 2025)
IntroductionOpen pancreaticoduodenectomy (OPD) and laparoscopic pancreaticoduodenectomy (LPD) are the two main surgical approaches for treating pancreatic cancer.ObjectiveTo evaluate the cost-effectiveness of OPD and LPD in treating pancreatic ductal adenocarcinoma by establishing a Markov Model.MethodsPatients with pancreatic ductal adenocarcinoma who staged at I-III undergone OPD or LPD were retrospectively included from March 2017 to December 2020. Patients were followed up by telephone until June 2024. A Markov Model was established to simulate disease progression after 120 cycles by including survival data and average hospitalization costs.ResultsTwo hundred patients were included, 100 for OPD group and the other 100 for LPD group. The results indicated that after 10 years of model operation, the LPD group had an increased cost of 13,175.31 yuan compared to the OPD group, with an incremental effect of 0.063 per quality-adjusted life years (QALY). It also showed that the incremental cost-effectiveness ratio value was ¥205,864.22per QALY, which was less than willing to pay (¥268,074.00).ConclusionThis study is the first to analyze the cost-effectiveness of OPD versus LPD in PDAC. The study indicated that LPD remains an acceptable operation with certain cost-effectiveness for pancreatic cancer patients. However, due to the low survival rates and the fact that LPD is a highly technique-dependent operation for pancreatic cancer, surgeons should keep cautious of the choice between the OPD and LPD based on the patient’s expectation and financial situation.